1997
DOI: 10.1007/s002130050189
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and pharmacodynamics of adinazolam: multi-ethnic comparisons

Abstract: The pharmacokinetics and pharmacodynamics of adinazolam and N-demethyladinazolam (NDMAD), its major active metabolite, were compared in 39 healthy male volunteers (13 Asian, 12 Caucasian and 14 African-American). In a four-way, double-blind crossover design, subjects were administered (1) 30 mg oral adinazolam mesylate SR tablets, (2) 10 mg parenteral (i.v.) adinazolam mesylate, (3) 30 mg i.v. NDMAD and (4) placebo. Venous blood samples were collected at specific time intervals after drug administration and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Therefore, intestinal metabolism of adinazolam substantially contributes to incomplete adinazolam oral bioavailability. Previous studies demonstrated that pharmacokinetic parameters for adinazolam and NDMAD can vary with age and across ethnic groups 6,35 . In this study, we demonstrated that pharmacokinetic parameters for adinazolam, NDAMD, and alprazolam in healthy male subjects are similar to those published previously 9–11 …”
Section: Discussionsupporting
confidence: 87%
“…Therefore, intestinal metabolism of adinazolam substantially contributes to incomplete adinazolam oral bioavailability. Previous studies demonstrated that pharmacokinetic parameters for adinazolam and NDMAD can vary with age and across ethnic groups 6,35 . In this study, we demonstrated that pharmacokinetic parameters for adinazolam, NDAMD, and alprazolam in healthy male subjects are similar to those published previously 9–11 …”
Section: Discussionsupporting
confidence: 87%
“…Another study compared adinazolam in Asians (Japanese, Chinese, Filipinos) versus Caucasians and African Americans after both oral and IV administration. 122 This study was well conducted and showed greater exposure of adinazolam in Asians, but no pharmacodynamic differences were seen (using observer sedation scores and the digit symbol substitu-tion test). Finally, nitrazepam was compared in Caucasians and Japanese.…”
Section: Benzodiazepinesmentioning
confidence: 70%
“…This study was rather small ( n = 8 in each group) and revealed no pharmacodynamic differences, although a higher C max was observed in Asians. Another study compared adinazolam in Asians (Japanese, Chinese, Filipinos) versus Caucasians and African Americans after both oral and IV administration 122 . This study was well conducted and showed greater exposure of adinazolam in Asians, but no pharmacodynamic differences were seen (using observer sedation scores and the digit symbol substitution test).…”
Section: Resultsmentioning
confidence: 99%
“…Benzodiazepine metabolism was shown to be different in Asian and Caucasian patients. Asian patients have a higher maximum plasma concentration, a larger area under the plasma concentration–time curve, and lower systemic clearance . One study did not show any significant difference, possibly because of its smaller sample size .…”
Section: Discussionmentioning
confidence: 99%